David du Plessis and the Assemblies of God : the struggle for the soul of a movement - Ziefle, Joshua R. (Global Pentecostal and Charismatic Studies, 2013)
In David du Plessis and the Assemblies of God Joshua R. Ziefle details the complicated tensions that arose during the Charismatic Movement of the 1960s and 1970s. He highlights the story of Pentecostal missionary David du Plessis, whose deep involvement in every area of the revival illustrates the tenor of the movement and the controversies it engendered. Du Plessis's ejection from the ministerial ranks of the Assemblies of God over his continued involvement with non-Pentecostals and the denomination's slow but steady rapprochement with the ecumenism of the Charismatic Movement are important themes in this monograph. Ultimately, Ziefle argues that both du Plessis's enthusiastic embrace of charismatics and the Assemblies' own hesitant approach to Spirit-filled Roman Catholics and mainline Protestants represent persistent hallmarks of Pentecostalism.